Pedagogical Aspects of the Development of Analytical Thinking in Students - Jamolova Gulbanbegim Muzaffar qizi; Muhammadiyeva Elmera Normurodovna (Scientific Trends, 2025)
This article analyzes the theoretical and practical aspects of the development of analytical thinking in students. The development of analytical thinking skills is considered as one of the main goals of the modern educational process, in this regard successful international experiments, pedagogical approaches and methodological technologies are highlighted. The author studies the essence of analytical thinking, the problems in the process of its formation and their solutions, as well as innovative methods used in the training and education of students. The article examines effective methods of developing analytical thinking based on the scientific views and approaches of famous scientists such as John Dewey, Jean Piaget, Francis Galton.
Keywords: Analytical thinking, pedagogy, problem education, interactive methods, intelligence, innovation, training technologies.